Class war or class welfare? The red shirt siege in Bangkok - Antonio L Rappa (2011)
Abhisit Vejjajiva prevented the worse excesses from engulfing the rest of the country. The prime minister has the coalition parties, the army, civil society groups, the Privy Council, and the Royals